2014
DOI: 10.1007/s00894-014-2156-1
|View full text |Cite
|
Sign up to set email alerts
|

Homology modeling, molecular dynamics and atomic level interaction study of snake venom 5′ nucleotidase

Abstract: 5' Nucleotidase (5' NUC) is a ubiquitously distributed enzyme known to be present in snake venoms (SV) that is responsible primarily for causing dysregulation of physiological homeostasis in humans by inducing anticoagulant effects and by inhibiting platelet aggregation. It is also known to act synergistically with other toxins to exert a more pronounced anti-coagulant effect during envenomation. Its structural and functional role is not yet ascertained clearly. The 3D structure of snake venom 5' nucleotidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The involvement of N. naja venom 5′NUC in inducing anticoagulant effect was demonstrated by the use of specific inhibitor, vanillyl acid (VA) . Our recent molecular docking interaction studies of snake venom 5′NUC with various inhibitors showed that structural analog of vanillin and VA differentially interacted and inhibited . In this study, we checked VMA inhibitory action on venom 5′NUC belonging to three different families, and thus its use as a biochemical or pharmacological tool to evaluate the role of enzyme 5′NUC in snake envenomation strategies is exemplified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of N. naja venom 5′NUC in inducing anticoagulant effect was demonstrated by the use of specific inhibitor, vanillyl acid (VA) . Our recent molecular docking interaction studies of snake venom 5′NUC with various inhibitors showed that structural analog of vanillin and VA differentially interacted and inhibited . In this study, we checked VMA inhibitory action on venom 5′NUC belonging to three different families, and thus its use as a biochemical or pharmacological tool to evaluate the role of enzyme 5′NUC in snake envenomation strategies is exemplified.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is widely accepted that 5′NUC plays an important role in snake envenomation strategies, apart from its hemostatic functions modulation, its other pharmacological effects are not well characterized . Several studies have used specific inhibitors of enzymes as a biochemical or pharmacological tool to characterize/or establish its mechanism of action .…”
Section: Resultsmentioning
confidence: 99%
“…Structural characterization and binding site prediction of SV‐5′ NUC1 from Demansia vestigiata revealed a predicted site comprising amino acids Y 65 and T 72 , which seemed to be Y 67 and T 76 for Cc‐5′NTase. In fact, vanillyl mandelic acid forms hydrogen bond with Y 65 , whereas vanillic acid forms hydrogen bonds with Y 65 and T 72 . Vanillic and vanillyl mandelic acids seemed to interact with Y 67 and T 76 of Cc‐5′NTase.…”
Section: Discussionmentioning
confidence: 98%
“…3D structures of all possible stereoisomer forms of synthesized compounds (ligands) were generated using the Marvin sketch [30] software package and were MM2 optimized using Discovery Studio 3.5. The bioavailability of compounds 6a, 6b, 6c, 6d, 6e, 6f, 7a, 7b, 7c, 7d, 7e and 7f was assessed using ADME (Adsorption, Distribution, Metabolism Elimination) program [31].…”
Section: In-silico Molecular Docking Studiesmentioning
confidence: 99%